Social and cultural context of the developpment of ukrainian-language studies in Canada in the last quarter of XX and at the beginning of XXI century - Mashkova, Inna (ScienceRise: Pedagogical Education, 2017)
In the article is given the historical-pedagogical analysis of the education in Ukrainian-language studies development in Canada in the last quarter of XX and at the beginning of ХХІ century. The socio-political, cultural and educational conditions of this development are characterized. Having considered the preconditions of official bilingualism and multiculturalism in Canada in the context of Ukrainian-language studies, the author conventionally separates three main periods with most typical socio-cultural factors that favored its development. The result of efforts and recommendations of Ukrainian Canadian teachers in 1960-ies became both changes, introduced to the school law and new cultural policy of Manitoba and Alberta provinces that accelerated the spread of multiculturalism in whole Canada. The period from 1971 to 1986 that is named in the research the beginning of official bilingualism and multiculturalism in Canada may be considered as very successful for the development of Ukrainian Canadians’ national education, because Ukrainian-language studies developed at all levels in this time (from preschool institutions to research ones). But at the end of 1980-ies the question about an aim of the national education appeared in Canadian diaspora. That is why the other period (1987–1998), from authors’ point of view, is characterized by the changes of the methodological paradigm on the base of innovative technologies in the context of intercultural interaction with Ukraine. We consider the special features of the third continuing period as the active participation of Ukrainian Canadians in the development of education in Ukraine, mutual influence of Canadian and Ukrainian methods of teaching disciplines on Ukrainian studies and deepening of international connections and cooperation between both countries in the context of further development of multicultural education throughout the world